Energy, exergy, and exergoeconomic analysis of a polygeneration system driven by solar energy with a thermal energy storage tank for power, heating, and freshwater production. (April 2021) - Xi, Zhang; Eshaghi, Soroush; Sardari, Farshid
Highlights: A solar-based trigeneration system for heating, power, and freshwater is proposed. Thermal energy storage (TES) tank is employed for performance improvement. A parametric study is investigated to understand the cycle performance better. The system could yield energy and exergy efficiencies of 34.78 %, 13.42 % . Total capital cost and total production cost are 92.13 / h and 176.73 / h . Abstract: A trigeneration system based on parabolic trough solar collectors and thermal energy storage tank is devised for simultaneous power, heating, and freshwater production. The proposed system is analyzed from energy, exergy, and exergoeconomic viewpoints. Moreover, a parametric analysis was applied to evaluate the effects of some basic thermodynamic parameters cycle performance. Also, the optimum performance of the system in two optimization scenarios is found by applying the multi-objective genetic algorithm and using LINMAP decision-making method. The results revealed that the system could yield net output power, heating capacity, and freshwater rate of 370.1 kW, 2423 kW, and 1.34 kg / s, respectively. The energy and exergy efficiencies, coefficient of performance, and the total cost rate of the product are obtained as 34.78 %, 13.42 %, 0.49, and 176.73 / h . Also, it is revealed that the solar section is responsible for 56 % of the overall exergy destruction rate. The parametric study showed that increment of pinch point temperature of RORC evaporator results in lower energy and exergy efficiencies and higher total cost rate of products. Also, the final optimal solution selected by the LINMAP method is a maximum exergy efficiency of 19.87 % and the minimum cost rate of 157.73 / h for the second optimization scenario.